PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MEMBINA PROFESIONALISME GURU - FITRIANI Fitri (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract: In carrying out his duties as a supervisor, the principal is obliged to help the teacher provide support so that he can carry out his duties properly. To carry out his professional duties, the teacher needs to understand and appreciate the form of the student as the person he will guide. On the other hand, the teacher must also understand and appreciate the form of the children of graduates as a picture of the results of their education expected by the community in accordance with the philosophy of life and the values adopted by the Indonesian people. In improving the quality of education education must be available that has professional experts or teachers. In other words, so that education can have more use and results of use and later expected to be able to answer the above problems, then the teacher still needs guidance and direction from the principal as the leader and the person in charge of the group Keywords: Principal as Supervisor and Teacher Professionalism